What influences media effects on public perception? A cross-national study of comparative agenda setting. (October 2019) - Vu, Hong T; Jiang, Liefu; Chacón, Lourdes M Cueva; Riedl, Martin J; Tran, Duc V; Bobkowski, Piotr S
Using a big data approach, this study explores the media agenda setting effects in 16 countries on five continents. Agenda setting effects were found to vary across the nations. Our findings provide empirical evidence that individual factors such as Age, Education, Living area, and Political ideology and national macro variables, including Economic development and Media freedom, are associated with the strength of such effects. Results suggest that assessing agenda setting effects needs to be conducted in relation to the economic, political, and media context of a country. This study also proposes an alternative way to measure salience on the public agenda using Issue distance, which arguably allows for capturing the possible interaction between issue relevance to individual audiences and media cueing effects.